Web components in action - Farrell, Ben (Manning Publications, 2019)
Web Components in Action teaches you to build and use Web Components from the ground up. You'll start with simple components and component-based applications, using JavaScript, HTML, and CSS. Then, you'll customize them and apply best design practices to maximize reusability. Through hands-on projects, you'll learn to build production-ready Web Components for any project, including color pickers, advanced applications using 3D models, mixed reality, and machine learning.